Intravitreal bevacizumab injections in a child with choroidal neovascularization – case report - Krzyżanowska-Berkowska, Patrycja; Barć, Anna; Oficjalska, Jolanta (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
A healthy 11 years old boy with active choroidal neovascularization (CNV) was referred to the Department of Ophthalmology in Wroclaw for unilateral visual deterioration from 2 weeks. The best-corrected visual acuity was counting fingers from 4 meters. Boy was successfully treated with three intravitreal injections of bevacizumab. Intravitreal bevacizumab was well tolerated, choroidal neovascularization involuted, and best-corrected visual acuity improved to 20/32. The boy remained stable for 6 months after injections.